Targeting S100 Calcium-Binding Proteins with Small Molecule Inhibitors - Wilder, Paul T. (Methods Mol Biol, 2019)
S100B is a small, dimeric, calcium-binding protein that is implicated in various diseases, most significantly cancer; therefore, there is interest in identifying S100B inhibitors that may have therapeutic value (Bresnick et al. Nat Rev Cancer 15:96–109, 2015; Chong et al. Curr Med Chem 23:1571–1596). Two fiuorescence polarization competition assays (FPCA) are described here for S100B and S100A1 that are amenable to high-throughput screening (HTS) campaigns and can be used to determine the binding affinity (K(i)) of the inhibitors. One FPCA is used to identify and characterize inhibitors of S100B with the aim of finding new therapeutics, and the other was developed as a counter-screen to avoid inhibitors of S100A1 due to its role in regulating skeletal and cardiac muscle function. Also outlined are methods for expressing and purifying S100B and S100A1 in quantities needed for performing large HTS campaigns.